ENVIRONMENTAL - BALANCED SCORECARD SEBAGAI STRATEGI DALAM MENGHADAPI PERSAINGAN DI MASA MENDATANG - Werner R. Murhadi (Journal of Management and Business, 2002)
Present development in performance measurement only considers the financial aspects of company that focuses on the past performance or lag indicator. Companies need other indicators to be used as lead indicators, to look after future performance. It needs a new method to integrate goals and performance measurement in a company, and to achieve vision and mission of the company. Balanced Scorecard system included, performance measurement based on financial aspect and non-financial aspects.Besides using the Balanced Scorecard as performance measurement, some companies use it as a strategic management system to manage its strategy for the long term. The Balance Scorecard, still could not response rapid concerns of society in environmental problems. Increasing of environmental awareness in the global society makes companies should not consider only on four perspectives in Balanced Scorecard, but also on environmental perspectives on companies' environment. Company's vision, mission and strategy should be reflected and inspired in the five aspects in Environmental-Balanced Scorecard.Tight competition in the industry and people's concern in reducing pesticide in the environment compels a company to develop strategies which can be used to satisfy its stakeholder. Environmental-Balanced Scorecard implementation as a management strategic system will help the company developing its competitive strategy and will satisfy society's demand to overcome negative environmental impact from its product.